On the question of incentive debt payments to the state budget: grounds for exemption from criminal liability (Journal of actual problems of jurisprudence, 2018)
In this paper the author attempts to analyze the grounds for exemption from criminal liability in cases of evasion of mandatory payments to the budget and examine the possibility of introducing a special rule on the exemption from criminal liability in connection with the repayment of debt with tax evasion. The author proposes to accept this provision as a rehabilitative ground. This provision is offered as an incentive to increase payments to the state budget. The proposed recommendations are correspond for the problem of humanization of criminal policy, as set out in the Republic of Kazakhstan legal policy concept for the period from 2010 – 2020.Key words: exemption from criminal liability, tax evasion, customs duties and taxes, the right, the duty, rehabilitative grounds.